Impact assessment of metal corrosion on fuel reservoir carrying capacity - O. O. Lukyanchenko; Yu. V. Vorona; O. V. Kostina; O. V. Kuzko; O. A. Kyrychuk (Ukrainian Antarctic Journal, 2015)
То prevent the large-scale contamination at the Vernadsky Station the development of the automated early-warning system of the leak fuel possibility is predicted in the State Target Scientific-Technical Research Program in the Antarctic for 2011-2020. An important соmроnent of the system is а subsystem of control and visualization the tensioned-deformed condition of the 200 m3 reservoir construction providing the lack of the necessary technical documentation and of data bу the current thicknesses both walls and welds of reservoir. The impact of corrosion from diesel fuel was studied on the carrying capacity of the conditional reservoir model (CRM). Using the finite elements method, which is implemented in software complex NASTRAN, the mathematical modeling was carried out of the CRM nonlinear behavior considering thinning of its wall in the system with protective capacity under the static loads action. Six  options of the walls thinning were accepted in the various reservoir zones in 0.25, 0.5, 0.75, 1. 0, 1.25, 1.5 mm. Nonlinear calculations of the CRM both tension-deformed state and stability were carried out using the modified method of the incremental Newton-Raphson load. Studies have shown that thinning of the walls on 1.5 mm reduces the stock stability approximately in 30%, with the mахimum intensity for all options of wall thinning is observed in the lower zone of the СRМ with the protective capacity. The obtained results can bе immediately applied for analysis of the carrying capacity of the real reservoir construction after obtaining of the quantitative characteristics of the walls reservoir thicknesses and after the technical documentation development for the real reservoir construction.